Long-term arsenite exposure induces testicular toxicity by redox imbalance, G2/M cell arrest and apoptosis in mice. (1st January 2019) - Zeng, Qun; Yi, Huilan; Huang, Liqun; An, Quan; Wang, Hong
Highlights: Arsenite induced testicular toxicity due to long-term exposure in mice. Arsenite caused a severe oxidative damage in testes. Arsenite induced testicular apoptosis partially via the upregulation of Bax levels, especially the caspase-3 activation. Arsenite caused G2/M testicular cell arrest by the downregulation of cdc2 and cyclin B1 levels and the upregulation of p-cdc2. Testicular toxicity of high arsenite dose group was stronger than that of low arsenite dose group. Abstract: Inorganic arsenic (iAs), a ubiquitous element and a natural drinking water contaminant, has been found to impair male reproductive function. However, the effect of long-term exposure to arsenic on testis damage and its underlying mechanisms still require further evaluation. In the study, male C57BL/6 mice (4 weeks) were treated with sodium arsenite at the doses of 5 or 50 ppm arsenic via drinking water for 180 days. Sperm count, histology in testes, oxidative stress biomarkers, cell cycle progress and apoptosis were assessed. Our results showed that arsenite seriously destroyed the structure of the testes and reduced the sperm count. Arsenite significantly decreased the activity of total superoxide dismutase (T-SOD) and glutathione (GSH) content but increased the levels of reactive oxygen species (ROS) and malondialdehyde (MDA) in testes. Furthermore, arsenite could induce G2/M phase arrest in testes, concurrent with a significant decrease in mRNA and protein levels of cdc2 and cyclin B1, the upregulation of p-cdc2, and an increase in mRNA levels of p53 and p21. Arsenite induced testicular apoptosis with a significant increase in Bax mRNA and protein levels, especially the caspase-3 activation. Testicular toxicity of the high dose group was stronger than that of the low dose group. In conclusion, testicular toxicity due to long-term exposure to arsenite may relate to oxidative damage, G2/M arrest and promoted apoptosis in the testes of mice, which contributed to the increased risk of spermatogenesis disorders and male infertility.